The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1080/08897077.2015.1052868
|View full text |Cite
|
Sign up to set email alerts
|

A Demonstration Project Implementing Extended-Release Naltrexone in Los Angeles County

Abstract: These findings reflect a higher XR-NTX cessation rate and a lower average number of doses, in contrast to similar demonstration projects in community settings with patients on parole or probation. However, this study shows that it is feasible to engage treatment providers in the use XR-NTX among their patients with alcohol or opioid use disorders. Several implications for future research and implementation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Participants coming from longer-term detoxification programs (mean duration = 35.1 days, SD = 27.5) were substantially more likely to be inducted on XR-NTX compared to participants coming from shorter-term detoxification programs (mean duration = 7.0 days, SD = 4.9). This finding is consistent with observational data collected in an XR-NTX implementation study in Los Angeles, CA that found patients receiving XR-NTX were significantly more likely to have been referred from residential treatment (47.5% vs. 16.5%) and less likely to have been referred from outpatient treatment (32.5% vs. 67.5%) than patients who did not receive XR-NTX (Cousins, et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Participants coming from longer-term detoxification programs (mean duration = 35.1 days, SD = 27.5) were substantially more likely to be inducted on XR-NTX compared to participants coming from shorter-term detoxification programs (mean duration = 7.0 days, SD = 4.9). This finding is consistent with observational data collected in an XR-NTX implementation study in Los Angeles, CA that found patients receiving XR-NTX were significantly more likely to have been referred from residential treatment (47.5% vs. 16.5%) and less likely to have been referred from outpatient treatment (32.5% vs. 67.5%) than patients who did not receive XR-NTX (Cousins, et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the preceding RCT phase and other XR‐NTX studies , the majority of the adverse events were withdrawal‐related and reported following the first administration of XR‐NTX . While we administered the first XR‐NTX injection after a minimum 72 hours of complete abstinence from any opioids, other studies have recommended a longer period of abstinence . Extending the number of opioid‐free days would have reduced the amount of adverse events and eased the induction phase.…”
Section: Discussionmentioning
confidence: 67%
“…This long‐acting formulation can be given in a wide range of clinical settings, including primary care and criminal justice systems 13, 14. However, there is limited experience with this drug medication outside specialized treatment settings.…”
Section: Introductionmentioning
confidence: 99%